Factors associated with blood pressure in end stage renal disease patients receiving regular hemodialysis at Wangaya general hospital, Denpasar - Nugraha, I. Kadek Aditya; Tedjamartono, Theodore Dharma; Sunaka, Wayan (International Journal of Advances in Medicine, 2021)
Background: Hypertension is common findings in end-stage renal disease (ESRD) patients receiving hemodialysis, around two third among them are poorly controlled. We analyzed factors affecting blood pressure in patients undergoing regular hemodialysis. Methods:A single center cross-sectional study conducted including 65 patients receiving regular hemodialysis at hemodialysis unit Wangaya general hospital, Bali, Indonesia. Ordinal regression test was performed to analyze the relationship between factor associated with blood pressure in regular hemodialysis patients. Results: Among subjects included, 64 (98.5%) subject had hypertension and 22 (34.4%) subjects had well controlled blood pressure (<140/90 mmHg), 20 (31.3%) subjects had blood pressure between 140/90 to 160/100 mmHg and 22 (34.4%) subjects had blood pressure >160/100 mmHg. Univariate analysis showed statistically significant associated factors were higher number of antihypertensive medications (p=0.002), higher level of hemoglobin (p=0.008), hematocrit (p=0.012) and urea (p=0.041). Multivariate analysis showed higher amount of anti-hypertensive medications and year of dialysis were statistically significant associated with blood pressure in regular hemodialysis patients. Conclusions:Significant factors associated with blood pressure in regular hemodialysis patients were higher amount of anti-hypertensive medications and increased year of dialysis.